2018
DOI: 10.1016/j.jdent.2018.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Water-associated attributes in the contemporary dentin bonding milieu

Abstract: The advent of the user friendly universal adhesives has brought forth significant changes to the dental adhesion arena. However, the elements that are critical for making resin-dentin bonds more durable to environmental challenges and less susceptible to degradation have remained unchanged at large.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…Permeability evaluation was conducted on resin-dentin interfaces bonded with 20-cm water pressure (Pucci et al 2018). Water permeability setup and examination procedures are included in the Appendix.…”
Section: Methodsmentioning
confidence: 99%
“…Permeability evaluation was conducted on resin-dentin interfaces bonded with 20-cm water pressure (Pucci et al 2018). Water permeability setup and examination procedures are included in the Appendix.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro bonding was performed using 20 cm H 2 O of stimulated hydrostatic pulpal pressure (Appendix Fig. 6) (Pucci et al 2018). The crown enamel was removed parallel to the occlusal surface under water cooling.…”
Section: Methodsmentioning
confidence: 99%
“…Since the introduction of the adhesive systems, over 50 years ago, the union interface to dentin remains the weakest link in restorative treatment [1][2][3][4] . Although many studies have shown excellent short-term and immediate adhesion effectiveness 5,6 , the durability and stability of the adhesive interface on dentin remain questionable 7,8 due to its inherent characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have shown excellent short-term and immediate adhesion effectiveness 5,6 , the durability and stability of the adhesive interface on dentin remain questionable 7,8 due to its inherent characteristics. The failure of adhesion may lead marginal infiltration, which may cause discoloration, secondary caries, and subsequent loss of retention 3,9,10 . In order to minimize adhesive failures, universal adhesives have become a trend in dentistry due to its effectiveness and longevity, and a simplified operative technique.…”
Section: Introductionmentioning
confidence: 99%